2022
DOI: 10.1186/s12891-022-05973-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the global prevalence and incidence of shoulder pain

Abstract: Background and objectives Studies reporting on the population burden of people living with shoulder pain show wide heterogeneity in terms of case definition, study samples, and occurrence. This systematic review aims to summarize evidence pertaining to the prevalence and incidence of shoulder pain, including variability based on sex and geography. We also explored the potential influence of methodological limitations and important sources of heterogeneity (case definition and reference period) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 17 publications
0
42
0
4
Order By: Relevance
“…In 2019, the Philippines had one of the highest burdens of neck pain around the world, with an age-standardized point prevalence of 5,333.5 per 100,000 population, and an annual incidence rate of 1,156.3 per 100,000 population (Shin et al 2022). From a global perspective, the age-standardized median prevalence of neck pain and shoulder pain was 27.0 per 1,000 and 37.8 per 1,000, respectively (Kazeminasab et al 2022; Lucas et al 2022). However, because the majority of people do not seek treatment for their problem, it is critical to assess the prevalence of shoulder discomfort in order to examine its influence on the population (Pribicevic 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the Philippines had one of the highest burdens of neck pain around the world, with an age-standardized point prevalence of 5,333.5 per 100,000 population, and an annual incidence rate of 1,156.3 per 100,000 population (Shin et al 2022). From a global perspective, the age-standardized median prevalence of neck pain and shoulder pain was 27.0 per 1,000 and 37.8 per 1,000, respectively (Kazeminasab et al 2022; Lucas et al 2022). However, because the majority of people do not seek treatment for their problem, it is critical to assess the prevalence of shoulder discomfort in order to examine its influence on the population (Pribicevic 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder pain is a common self-reported musculoskeletal complaint with a median prevalence of 16% in general population, which increases in women and high-income countries 1 . It can lead to sick leave and difficulties in daily activities and it has a lifetime prevalence between 7 and 67% 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review has shown that, in the general population, the 1‐year prevalence of shoulder pain ranges from 4.7% to 46.7% depending on the study, while lifetime prevalence reaches 66.7% 1 . In a recent systematic review, Lucas et al 2 found that the community prevalence of shoulder pain varies widely across countries, with a median of 16% (range: 0.67%–55.2%). According to this study, the incidence of shoulder pain ranges from 7.7 to 62 per 1000 people per year (median 37.8 per 1000 people per year 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review, Lucas et al 2 found that the community prevalence of shoulder pain varies widely across countries, with a median of 16% (range: 0.67%–55.2%). According to this study, the incidence of shoulder pain ranges from 7.7 to 62 per 1000 people per year (median 37.8 per 1000 people per year 2 . Meanwhile, Lewis et al 3 estimate that one in three people experience shoulder pain in their lifetime.…”
Section: Introductionmentioning
confidence: 99%